Fostering Teacher and Educational Staff Work Motivation to Improve Competence at Nurul Iman Private Junior High School - Mustika, Anik Indra; Muslim Liyadi; Lubis, Nasib Samsuri; Mira Santika; Afriza (Journal of Practice Learning and Educational Development, 2025)
This study aims to find out the work motivation of teachers at Nurul Iman Private Junior High School. Based on data obtained through interviews on December 9, 2024, the results of the study show that the work motivation of teachers at Nurul Iman Private Junior High School is still relatively low. This is due to the lack of effective communication between principals and teachers, limited support in the development of professionalism, and the lack of awards and incentives. These factors affect teacher satisfaction and performance, so steps are needed to increase work motivation, both through the management of intrinsic and extrinsic factors. Principals who are able to build trust, communicate the school's vision and mission, support competency development, recognize teachers' contributions, and make fair decisions can create a positive environment and motivate educators to work better. The high motivation of teachers contributes to improving the quality of learning, achieving educational goals, and creating a better working environment. In addition, motivation can also reduce stress levels, increase job satisfaction, strengthen team collaboration, and improve overall school performance. This research also highlights the importance of two motivational factors, namely intrinsic and extrinsic factors, which need to be managed properly by school principals to achieve optimal educational goals. By implementing the right motivational strategies, school principals can create significant changes in the quality of education in the school.